Exchange rate expectations since the financial crisis: Performance evaluation and the role of monetary policy and safe haven - Joscha Beckmann; Robert Czudaj (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We analyze and evaluate novel data on exchange rate expectations after the collapse of Lehman Brothers for more than 60 economies over different horizons. We find that monetary policy effects on expectations are time-varying and identify substantial international spillovers over the recent period. Our results also show that markets have been surprised by monetary policy effects on the exchange rates and point to an unexpected safe haven status of the US dollar after 2009.
Keywords: F31; G15; 330